Detection of Non-Cytopathic Enteroviruses in Supernatant of RD and L20B Cell Cultures (2020)
We investigated the likely presence of enteroviruses in supernatants of cytopathic effect (CPE) negative RD and L20B cell culture tubes in which faecal suspension from acute flaccid paralysis (AFP) cases were cultured. Samples analyzed were collected in 2017 as part of the AFP surveillance program in Nigeria and declared negative for enteroviruses because they did not produce CPE in RD and L20B cell lines. In all, 120 cell culture supernatants (60 each on RD and L20B cell lines) that emanated from 30 stool suspensions (2 samples per case) were analyzed as 60 pools (pooled per case by cell line). Pools were subjected to RNA extraction, RT-snPCR, amplicon sequencing and phylogenetic analysis. Eleven and one of the 30 pools of RD and L20B cell culture supernatants, respectively, were positive for the RT-snPCR. Nine of the 11 amplicons from RD and the only from L20B were sequenced and identified as seven EV types; Coxsackievirus A4 (CVA4), CV-A6, CV-A13, CV-A17 (both RD and L20B), CV-B2, Echovirus 9 (E9) and Enterovirus A76 (EVA76). Our findings suggest some enteroviruses are present in and might be replicating in RD cell line without producing CPE. We also report the existence of CV-A6 genotype E (possibly sub-Saharan Africa restricted).